ANALISIS PENGARUH INTERPERSONAL COMMUNICATION TERHADAP PERSON ORGANIZATION FIT DAN IMPLIKASINYA PADA PRESTASI KERJA - Hadiwijaya, Hendra (International Journal of Social Science and Business, 2017)
Analysis of interpersonal communication to fit people organization and its implication on work achievement to know and analyze the direct influence of interpersonal communication to people Fit Organization And Its Implication On Job Performance of Inspectorate Employee of South Sumatera Province. This analysis uses Structural Equation Modeling (SEM). The results showed that the influence of Interpersonal Communication (IC) variable to Person Organization Fit (POF) is 0.53, Interpersonal Communication (IC) to Job Performance of -0.04 and Person Organization Fit (POF) on Job Performance of 1.00. Indirect Influence Interpersonal Communication Variables (IC) To People Organization Fit (POF) And Its Implication On Job Performance (PK) employee Inspectorate Province of South Sumatra equal to 0,53.